Persistence Analysis on Pre-coalition Models of H1N1-p with H5N1 virus in L 2 Space - Hariyanto Hariyanto; Mahmud Yunus; Gusti Yuni Shinta Lestari (LPPM Institut Teknologi Sepuluh Nopember, 2016)
Influenza virus, H1N1-p and H5N1, are dangerous viruses. Medium of virus transmissions is the interaction or contact between individuals. The virus transmission to other individuals is easy. This happens due to a new strain that occurs as a result of pre-coalition between the two viruses. That phenomena is formulated in the form of a pre-coalition model of the virus. From the original pre-coalition model, a reduction process is done such that the models can be analyzed easily. Furthermore, the reduced pre-coalition model will be analyzed (i.e. existence and uniqueness of solutions), so that the system of equations is said to be well-posed. Persistence analysis result shows that in an unstable condition, H1N1-p influenza virus is “strongly uniformly persistence” over the system under the assumption that the H5N1 influenza virus is in a steady state. A similar result is also true for the H5N1 influenza virus. The H5N1 virus is more pathogenic than the H1N1-P-p. This is indicated by the value of epsilon0 in H5N1 virus is smaller than in H1N1-p virus, where epsilon0 shows the distance of interactions between individuals.